Scientism and Education Empirical Research as Neo-Liberal Ideology - Hyslop-Margison, Emery J.; Naseem, Ayaz (Springer Netherlands : Imprint: Springer, 2007)
This volume offers a critical examination of the growing pressure to apply scientific principles as a means to improve education. The authors trace the ideology of scientism to the early faith Auguste Comte placed in science and the scientific method as a panacea to all human problem solving. By revealing many of the epistemological problems confronted by the social sciences, including education, the authors undermine the prevailing view that a science of education is possible or desirable. Besides revealing the epistemological problems associated with education research, they suggest that the instrumentalism and micro level responsibility related to scientism in education constitute a manipulative ideological smokescreen to distract public attention away from the structural inequities that generate disparate academic outcomes among students in industrialized democracies. The book deals a severe blow to the belief that science is a suitable lens through which to view or strengthen educational practice. "One begins this book with the skeptical belief that it can't be right. The task of reading, then, is to locate where Hyslop-Margison goes wrong to reach his radical and disturbing conclusions. At the very least, even the most skeptical will have to recognize that the unsayable-that current educational research has proven largely fruitless for discernable reasons-is certainly plausible. He brilliantly brings an issue that has been considered too eccentric to contemplate into the heart of current educational discourse. Everyone concerned with educational research-researchers and those policy-makers, administrators, and other educational workers who draw on the products of educational research should read this important book carefully." Kieran Egan, Faculty of Education, Simon Fraser University.